Polyamory: Intimate practice, identity or sexual orientation?. (January 2014) - Klesse, Christian
Polyamory means different things to different people. While some consider polyamory to be nothing more than a convenient label for their current relationship constellations or a handy tool for communicating their willingness to enter more than one relationship at a time, others claim it as one of their core identities. Essentialist identity narratives have sustained recent arguments that polyamory is best understood as a sexual orientation and is as such comparable with homosexuality, heterosexuality or bisexuality. Such a move would render polyamory intelligible within dominant political and legal frameworks of sexual diversity. The article surveys academic and activist discussions on sexual orientation and traces contradictory voices in current debates on polyamory. The author draws on poststructuralist ideas to show the shortcomings of sexual orientation discourses and highlights the losses which are likely to follow from pragmatic definitions of polyamory as sexual orientation.